INTENSITAS KONSUMSI PANGAN LOKAL SUMBER KARBOHIDRAT NON BERAS DALAM UPAYA DIVERSIFIKASI PANGAN DI DESA HARGOREJO KECAMATAN KOKAP KABUPATEN KULON PROGO - Mutakin, Deden (Jurnal Pendidikan Geografi Gea, 2017)
This research aimed to analyze the intensity of consumption of local food sources of carbohydrates non-rice in the fulfillment of energy and protein according to the number recommended dietary pattern hope WKNPG VIII 2004 and to see the extent of community efforts in diversification efforts carbohydrate source non-farm household and farm in the hamlet of East and Ngulakan Selo Village Hargorejo District Kokap. By multistage sampling method and Slovin formula obtained a sample of 120 people. Based on the review concluded non-farm households and farmers are not applying food diversification in daily consumption. The intensity of consumption of local food sources of carbohydrates non-rice is still very low or not in accordance with the recommended figure.